2012
DOI: 10.1121/1.3683251
|View full text |Cite
|
Sign up to set email alerts
|

Time reversed elastic nonlinearity diagnostic applied to mock osseointegration monitoring applying two experimental models

Abstract: This study broadens vibration-like techniques developed for osseointegration monitoring to the nonlinear field. The time reversed elastic nonlinearity diagnostic is applied to two mock models. The first one consists of tightening a dental implant at different torques in a mock cortical bone; the second one allows one to follow glue curing at the interface between a dental implant and a mock jaw. Energy is focused near the implant interface using the time reversal technique. Two nonlinear procedures termed puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…3,6 A nonlinear resonant method, 6 performed on a model made of two weakly damped materials, confirmed the greater sensitivity of the nonlinear response to the contact quality and demonstrated that a broad frequency band is useful to increase the sensitivity range. A more realistic interface composed of a dental implant and a bone phantom was then studied.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…3,6 A nonlinear resonant method, 6 performed on a model made of two weakly damped materials, confirmed the greater sensitivity of the nonlinear response to the contact quality and demonstrated that a broad frequency band is useful to increase the sensitivity range. A more realistic interface composed of a dental implant and a bone phantom was then studied.…”
mentioning
confidence: 86%
“…2 Among these measurements and as detailed in Ref. 3, nonlinear elasticity could be of interest in providing information regarding contact integrity because the nonlinearity likely comes from frictional effects and/or clapping sources. Several groups have attempted measurement of nonlinear parameters at an interface bone/hip prosthesis.…”
mentioning
confidence: 99%
See 3 more Smart Citations